Analisis Faktor Risiko Status Kematian Neonatal Studi Kasus Kontrol di Kecamatan Losari Kabupaten Brebes Tahun 2006 - Prabamurti, Priyadi Nugraha; Purnami, Cahya Tri; Widagdo, Laksmono; Setyono, Sigit (Jurnal Promosi Kesehatan Indonesia, 2008)
Background: The efforts to reach the national target to decreasing infant mortality, what in this time still become governmental priority programs. Nationally, mortality rate in this last decade had decreased excessively, from 50 per a thousand alive births in 2001 becoming 39 per a thousand alive births in 2005. The number revealed if seen at mortality neonatal still high enough.Method: This is an analytical survey research with case-control approach. Research subjects consists of 29 women having infant which die at neonatal age as a case group, and 29 women having alive infant passed a neonatal period, as a control group. Source of data obtained from secondary data to verbal autopsy record, history of pregnant woman and confinement note from public health center (Puskesmas). Data analyzing by univariate and bivariate analysis. Statistical test by Chi Square test that significance rate determined if p -value less than 0.05 and calculation of Odds Ratio (OR>1).Result: Result of analysis indicates that mother age (p = 0.0023 and OR = 7.69), parity (p =0.0006 and OR = 8.25), helper of confinement (p = 0.044 and OR = 6.07), born baby weight (p = 0.016 and OR=6,12) and condition of baby breathing effort (p= 0.001 and OR = 7.85), significantly risked to neonatal status. It is conclude that mother age, parity, helper ofconfinement, born baby weight and condition of baby breathing effort is risked to neonatal status. It is suggested to maturing marriage age and management of birth at healthy reproduction age, increasing of neonatal call so that can decreasing mortality rate.Keywords: neonatal mortality status, risk factors, pregnant woman